Influence of Alternative Conceptions on Upper Basic Education Students’ Interest in Basic Science and Technology in Benue State, Nigeria - Johnson Mhile Yaapera; James Musa Adejoh PhD; Okwara Kalu Okwara PhD; Abel Okoh Agbo-Egwu PhD (Journal of Advanced Research in Education, 2024)
This study investigated the influence of alternative conceptions on Upper Basic Education (UBE) students’ interest in Basic Science and Technology in Benue State, Nigeria. The study had three objectives and three research questions. Two research hypotheses were formulated and tested at 0.05 level of significance. The study was an ex-post facto descriptive research design. A total of 79,600 UBE 1 students in Benue State formed the population of the study. The sample used in the study was 398 students randomly sampled from three educational zones in Benue State. Basic Science Alternative Conceptions Identification Checklist (BSACIC) and Basic Science Alternative Conceptions Influence on Students’ Interest Questionnaire (BSACISIQ) were instruments for data collection. The reliability of the instruments were 0.74 and 0.87 for BSACIC and BSACISIQ respectively. Data were collected and analyzed using frequency count and percentages, means, standard deviations and student t-test. The findings of this study show that students held alternative conceptions in Basic Science and Technology, alternative conceptions significantly influenced students interest and there was no significant difference in the influence of alternative conceptions on male and female students’ interest in Basic Science and Technology. Based on these findings, it was concluded that UBE students have alternative conceptions that influence their interest in Basic Science and Technology, gender do not determines how alternative conceptions influence UBE students’ interest in Basic Science and Technology in Benue State. It was recommended that Basic Science and Technology Teachers should be conscious of the identified alternative conceptions held by students while teaching Basic Science and Technology. They should also apply appropriate teaching strategies for correcting students’ alternative conceptions in order to improve their interest in Basic Science and Technology in Benue State.